PROFIL IBU HAMIL YANG MELAHIRKAN DENGAN SEKSIO SESAREA DI RSU ROYAL PRIMA - Mangatas Silaen (Universitas Prima Indonesia, 2020)
Cesarian section is a technique of giving birth to the fetus through the incision of the abdominal wall (laparotomy) and the uterine wall (hysterotomy). According to WHO, the incidence of cesarean section is increasing in developing countries. In Indonesia alone, based on Riskesdas (Basic Health Research) in 2013, 9.8% of births were cesarean section method where the highest proportion was DKI Jakarta (19.9%) and lowest in Southeast Sulawesi (3.3%), while in North Sumatra ranges from 10-15%. The purpose of this study was to determine the profile of cesarean section at RSU Royal Prima Medan. This research method is descriptive research using cross sectional design. The sample was taken by simple random sampling technique and obtained 100 cesarean section patients. Data obtained from patient medical record data. The results showed the highest proportion of mothers with cesarean section in age group 27-31 years 33%, high school graduation 59%, housewife 60%, multigravida 36%, labor spacing> 2 years 58%, mother indication 50%, early rupture membrane with a history of recurrent sections 10%, fetal failure 3%, early rupture membranes with fetal failure 5%, average treatment duration of 4 days. It is expected that interested parties should be able to provide counseling on the regulation of the number and distance of labor and to improve the extension of good antenantal care supervision